2003
DOI: 10.1111/j.1527-5299.2003.03269.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antihypertensive Therapy With Fixed‐Dose Amlodipine Besylate/Benazepril HCl Versus Comparable Component‐Based Therapy

Abstract: Adhering to medication regimens has the potential to significantly improve clinical outcomes for persons with high blood pressure. A patient-related factor likely to affect adherence to treatment is the convenience of the prescribed drug regimen. The authors hypothesized that medication adherence would be superior and cost benefits would accrue in subjects who receive a once-daily, single-capsule, fixed-dose combination product for blood pressure control, compared with subjects who receive a similar regimen of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 45 publications
1
120
0
2
Order By: Relevance
“…2,15,40 In a recent study, subjects receiving a once-daily, fixed-dose combination of an ACE inhibitor and a dihydropyridine CCB demonstrated significantly greater compliance with their medication regimen, compared with subjects receiving a similar regimen containing an ACE inhibitor and a dihydropyridine CCB as separate drugs. 41 Wogen et al, in a previous study published in JMCP, found higher adherence with the ARB, valsartan, compared with amlodipine or lisinopril. 42 Approximately half of the patients in the present study were taking either ACE inhibitors or CCBs.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,15,40 In a recent study, subjects receiving a once-daily, fixed-dose combination of an ACE inhibitor and a dihydropyridine CCB demonstrated significantly greater compliance with their medication regimen, compared with subjects receiving a similar regimen containing an ACE inhibitor and a dihydropyridine CCB as separate drugs. 41 Wogen et al, in a previous study published in JMCP, found higher adherence with the ARB, valsartan, compared with amlodipine or lisinopril. 42 Approximately half of the patients in the present study were taking either ACE inhibitors or CCBs.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…18 In addition, several other studies have used 80% as a cut-off point when assessing compliance in HTN and other disease states as well. [19][20][21][22][23][24] Potential factors associated with adherence in this study included age, gender, prescription count of nonantihypertensive medications, and severity of illness adjusted according to the Charlson Comorbidity Index. The Charlson index contains 19 categories of comorbidities and includes scores from 0 to ≥6, according to the absence or presence of comorbid disorders, which are indicated by ICD-9 codes and was assessed up to 270 days prior to the date of the BP recording.…”
Section: Medication Possession Ratio and Other Measures Of Interestmentioning
confidence: 99%
“…Several studies have repeatedly demonstrated that patients are about 20% more likely to continue taking a 2-drug singlepill combination than they are the same 2 drugs prescribed as separate medications. 41 In the United States, 7 of the 8 commercially available ARBs are also available as single-pill fixed-dose combinations with the thiazide diuretic hydrochlorothiazide (HCTZ). A combination of the newest ARB, AZL, with the thiazide-like diuretic, chlorthalidone (CLD), is currently under FDA review.…”
Section: Arbs As Part Of Combination Therapymentioning
confidence: 99%
“…15,16 When combination therapy is administered, fixed-dose combinations are more convenient to patients and may improve treatment adherence. 17 A fixed-dose combination of an angiotensin receptor blocker (ARB) with a thiazide, typically hydrochlorothiazide (HCTZ), is a widely used strategy in hypertension management. However, there is a need for further data for ARB/thiazide fixed-dose combination therapy in patients with moderate hypertension, including in the context of initial therapy.…”
Section: Introductionmentioning
confidence: 99%